FirstLight IV: diversity in sub-L* galaxies at cosmic dawn. Issue 3 (28th April 2021) - Ceverino, Daniel; Hirschmann, Michaela; Klessen, Ralf S; Glover, Simon C O; Charlot, Stéphane; Feltre, Anna
ABSTRACT: Using a large sample of sub-L* galaxies, with similar UV magnitudes, MUV ≃ −19 at z ≃ 6, extracted from the FirstLight simulations, we show the diversity of galaxies at the end of the reionization epoch. We find a factor ∼40 variation in the specific star formation rate (sSFR). This drives a ∼1 dex range in equivalent width of the [O iii ]λ5007 line. Variations in nebular metallicity and ionization parameter within H ii regions lead to a scatter in the equivalent widths and [O iii ]/H α line ratio at a fixed sSFR. [O iii ]-bright ([O iii ]/H α>1) emitters have higher ionization parameters and/or higher metallicities than H α-bright ([O iii ]/H α<1) galaxies. According to the surface brightness maps in both [O iii ] and H α, [O iii ]-bright emitters are more compact than H α-bright galaxies. H α luminosity is higher than [O iii ] if star formation is distributed over extended regions. [O iii ] dominates if it is concentrated in compact clumps. In both cases, the H α-emitting gas is significantly more extended than [O iii ].